Penerapan Metode WASPAS dengan Pembobotan ROC Pada Pemilihan Graphic Designer - Agus Iskandar (STMIK Budi Darma, 2023)
A graphic designer is someone who is responsible for creating visual concepts using computer software. The concept is designed based on ideas that inspire and can captivate consumers in art and virtual forms in the form of pictures, words and other art forms. All companies will need a graphic designer in carrying out promotions, sales, recruitment or whatever will be closely related to graphic designers so that when recruiting and selecting graphic designers if it is done non-computerized it can cause losses for the company. To solve these problems, we need a system that is a decision support system. The use of decision support systems requires a method. In this study the method used is the WASPAS method with ROC weighting. The results of this study concluded that the one that meets the criteria as the best Graphic Designer is alternative A7, namely Dianiar with a value of 0.9424 as the first rank